Stimulation Of Linguistic Intelligence through Project Methods - Rizki, Dita Aulia (Early Childhood Research Journal (ECRJ), 2019)
The purpose of the study is to provide an overview and influence of the project method on the stimulation process of linguistic intelligence of children aged 4-5 years at the Bina Karsa Kindergarten in Lampung Province. The research method used is Action Research. Data collection techniques carried out through observation, interview stimulation of linguistic intelligence through project methods. Qualitative descriptive data analysis techniques, namely, a complete description of the process of linguistic intelligence stimulation activities through project methods and quantitative descriptive, the results of the percentage of the effect of the project method on the success of linguistic intelligence stimulation with stages through Cycle 1, Cycle 2 and so on. Samples selected by children aged 4-5 years at Bina Karsa Kindergarten. Sampling through interviews with teachers and direct observation. Linguistic intelligence is the intelligence of language intelligence in processing words or the ability to use words effectively both verbally and in writing. Project method is a project method is one method used to train children's ability to solve problems experienced by children in everyday life. Based on the pre-research results, it can be concluded that stimulation of linguistic intelligence through the activities and use of media in accordance with the activities of linguistic intelligence stimulation, and the method often used is the method of storytelling and play. The method of storytelling is not enough in the stimulation process, a trial using the project method is carried out.